[Installation of equipment at Brechin Castle Factory, Trinidad] - (:unkn) unknown (The Public Relations Department. Caroni (1975) Limited, Trinidad and Tobago, 2013)
Installation of the jaw on the front end of the loader at one of Caroni (1975) Limited'sfactories.
Cataloger's title
Keywords: Sugar factories -- Trinidad and Tobago; Sugar—Manufacture and refining—Equipment and supplies; Agricultural equipment -- Installation; Caroni (1975) Limited